Suppressive role of regucalcin in liver cell proliferation: involvement in carcinogenesis - Yamaguchi, M. (Cell Prolif, 2013)
Regucalcin (RGN/SMP30) was discovered in 1978 and is a unique calcium‐binding protein contains no EF‐hand motif calcium‐binding domain. Its name, regucalcin, was proposed as it suppresses activation of enzymes related to calcium signalling. The regucalcin gene (rgn) is localized on the X chromosome. Regucalcin plays its role of suppressor protein in intracellular signalling pathways, including of protein kinases and protein phosphatase activities, protein synthesis, and DNA and RNA synthesis in liver cells. Overexpression of endogenous regucalcin has a suppressive effect on cell proliferation in modelled rat hepatoma H4‐II‐E cells, which are induced by various signalling stimulations in vitro. This suppressive effect is independent of apoptosis. Endogenous regucalcin plays a suppressive role on overproduction of proliferating cells in regenerating rat liver in vivo. Regucalcin mRNA expression is uniquely down‐regulated in development of carcinogenesis in liver of rats in vivo. Regucalcin mRNA and protein expressions are also depressed in human hepatoma HepG2 cells, MCF‐7 breast cancer cells, and prostate cancer LNCaP cells. Depression of regucalcin expression may be associated with activity progression of carcinogens. Regucalcin may be a key molecule suppressor protein in cell proliferation and carcinogenesis.